Magnetic Hyperthermia in the 400–1,100 kHz Frequency Range Using MIONs of Condensed Colloidal Nanocrystal Clusters - Kouzoudis, Dimitris; Samourgkanidis, Georgios; Kolokithas-Ntoukas, Argiris; Zoppellaro, Giorgio; Spiliotopoulos, Konstantinos (Frontiers in Materials, 2021)
In the current study, we explored the magnetic hyperthermia performance of condensed–clustered magnetic iron oxide nanoparticles (MIONs) in the range of 400 kHz to 1.1 MHz at low field amplitudes. The strong interparticle interactions, present in such systems, can influence the hyperthermia power produced by MIONs. Herein, the heat dependence, as an increasing function of frequency, with a fixed magnetic field strength of 3 mT is recorded, revealing a direct relationship between the two physical quantities and a high heating efficiency for the condensed–clustered MIONs. In particular, the specific loss power (SLP) (or specific absorption rate [SAR]) parameter, which is the ratio of the heat power in watts produced per nanoparticle mass in grams, is linear to a good degree to the oscillating frequency with a step of roughly 30 W/g per 100 kHz increase. In addition, all the measurements were within the safety limits proposed by Hergt and Dutz criterion of H f ≤ 5 × 109A/ms for clinical application of magnetic fluid hyperthermia (MFH). Finally, the measured data of temperature vs. time at each frequency were interpreted in terms of simple thermodynamic arguments, thus extracting useful thermodynamic parameters for the heat power generated by the condensed–clustered MIONs.